Looking back at the parcoursArianna in the Val d'Anniviers - Thierry Amrein (Revue de Géographie Alpine)
When evoking development policies and projects, it is rare that Switzerland comes to mind. However the object of this text is a project conceived specifically for the women of the Swiss alpine valleys. This programme entitled parcoursArianna, aimed at the empowerment and stabilisation in their habitat of women considered greatly disadvantaged from the point of view of training and employment, due to their socio-geographical situation. The afore-mentioned objectives should have been attained thanks to the creation and deployment of an original “specifically feminine” micro-entrepreneurship within a local economic fabric essentially turned towards tourism.Starting from the results of a long-lasting anthropological field in the framework of this course of training, which also highlights the growing diversity of the populations in the Swiss alpine valleys, I question the fact that the initiators of this type of project implicitly make the women alone bear the responsibility and the charge of the new social dynamics which they attempt to initiate, without seriously taking into account the local norms of the sexual division of the tasks within the domestic sphere.